Biosynthesis of polyhydroxyalkanoate from food waste oil by Pseudomonas alcaligenes with simultaneous energy recovery from fermentation wastewater. (15th July 2021) - Pan, Lanjia; Li, Jie; Wang, Ruming; Wang, Yu; Lin, Qinghuai; Li, Chunxing; Wang, Yin
Graphical abstract: Highlights: The first report of PHA synthesized by Pseudomonas alcaligenes . Optimal conditions and scale-up production of mcl-PHA were achieved. Basic characteristics of mcl-PHA were analyzed to suggest its application. Energy was further recovered from the fermentation wastewater after extracting PHA. Abstract: Bioconversion of food waste oil (FWO) into biodegradable plastic is a promising method for converting waste into high-value products. In this study, a strain ( Pseudomonas sp. H3) was isolated for polyhydroxyalkanoate (PHA) synthesis from FWO. After 72 h of cultivation with 20 g/L of FWO, the high cell dry weight (CDW) of 3.6 g/L, PHA yield of 2.4 g/L, and PHA content of 65 wt% were obtained under the optimal temperature (25 °C) and inoculum amount (6% (v/v)). Fed-batch fermentation was conducted in a 5 L bioreactor with a maximum CDW of 16 g/L, PHA content of 54 wt%, and PHA productivity of 0.23 g/(L·h) after 36 h. The PHA had a molecular weight of 54 782 Da and a low polydispersity index of 1.41 with glass transition, melting, and degradation temperatures of −20 °C, 34 °C, and 210 °C, respectively. To further utilize the wastewater after PHA production, anaerobic digestion was employed for CH4 production, and the CH4 yield was 284 mL/g volatile solids. Microbial community analysis showed that the abundance of acetate-oxidizing bacteria and Methanobacterium significantly increased during anaerobic digestion. This study describes a new strain for the economical synthesis of biodegradable plastics and presents a novel framework for fully utilizing FWO with the production of PHA and CH4 .